A visit to Lahore: experiencing residential care in another culture - Andrew Hosie (Scottish Journal of Residential Child Care)
Children in Pakistan face a variety of serious challenges ranging from malnutrition and poor access to education and health facilities to exploitation in the form of child labour (UNICEF, 2007). In particular, many children are at risk of being orphaned due to natural disasters or poor life expectancy. As such, residential care is a necessity in Pakistan. I was given the opportunity to visit to a residential setting in Pakistan run by SOS Children’s Villages, an international non-governmental organisation (NGO) that has been active in the field of children's services since 1949 and provides services in over 130 countries. SOS Children's Villages focuses on family-based, long-term care of children who can no longer grow up with their biological families (SOS, 2007). In Pakistan, as in many developing countries, central government works in partnership with international NGOs to enable it to provide services such as residential care.